1999
DOI: 10.1164/ajrccm.159.3.9801052
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus and Respiratory Syncytial Virus in Wheezing Children Requiring Emergency Care

Abstract: This cross-sectional emergency department study of 70 wheezing children and 59 control subjects (2 mo to 16 yr of age) examined the prevalence of respiratory viruses and their relationship to age, atopic status, and eosinophil markers. Nasal washes were cultured for respiratory viruses, assayed for respiratory syncytial virus (RSV) antigen, and tested for coronavirus and rhinovirus RNA using reverse transcription-PCR (RT-PCR). Also evaluated were eosinophil numbers and eosinophil cationic protein (ECP) in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

37
394
5
14

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 417 publications
(450 citation statements)
references
References 23 publications
37
394
5
14
Order By: Relevance
“…Tree pollen levels in the Charleston area are highest in April, weed pollen levels are highest in October, and peak rhinovirus activity is highest in the fall and spring in nearby areas. [23][24][25] These seasonal associations would not, however, account for the long-term trend found in this study.…”
Section: Discussionmentioning
confidence: 64%
“…Tree pollen levels in the Charleston area are highest in April, weed pollen levels are highest in October, and peak rhinovirus activity is highest in the fall and spring in nearby areas. [23][24][25] These seasonal associations would not, however, account for the long-term trend found in this study.…”
Section: Discussionmentioning
confidence: 64%
“…Exacerbations, the worsening of asthma symptoms, are a growing public health concern, resulting in millions of missed work and school days and $50 billion in direct healthcare costs in the United States each year (3)(4)(5). Prior studies have examined environmental correlates of asthma exacerbations, including air quality measures (6)(7)(8), whereas others have considered the role of respiratory virus infections in triggering asthma exacerbation (9)(10)(11)(12)(13). However, none have simultaneously considered both infectious and noninfectious factors that potentially influence the large-scale spatiotemporal dynamics of asthma exacerbations.…”
mentioning
confidence: 99%
“…12,16 The limited number of patients in the present study was probably the result of the rigorous criteria used to define the acute episode as the first in the childs life and of the use of a single center, but we believe that it is representative of the population of infants who visit the emergency care rooms and hospital infirmaries in the city of Porto Alegre.…”
Section: Discussionmentioning
confidence: 95%
“…[9][10] Furthermore, upper airway infections by this virus have been associated with episodes of asthma exacerbation in older children and adults. [11][12] Nevertheless, Papadopoulos et al 13 demonstrated that RV may also cause lower airway infections. Previous studies have demonstrated an association between RV infection and wheezing in infants.…”
Section: Introductionmentioning
confidence: 99%